2015
DOI: 10.1089/vim.2014.0135
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Immunodominance of Virus-Specific T Cell Responses During Hantaan Virus Infection

Abstract: Immunodominant T cell responses are important for protection against virus challenge. However, studies screening for the immunodominant T cell responses and following their kinetics in acute Hantaan virus (HTNV) infection are very limited. Herein, the HTNV nucleocapsid protein-specific T cell responses were longitudinally screened in 15 patients with acute HTNV infection, eight of whom had a particularly severe hemorrhagic fever with renal syndrome (HFRS). An extremely impaired IFN-γ-producing T cell response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In a mouse model of persistent infection, almost no IFN-γ-producing T cells were detected, while mice with transient infection showed increased functional HTNV-specific CTLs ( 23 , 47 ). HTNV-specific T-cell responses in patients with severe HFRS were heavily impaired at the early stage of infection, indicating that an initial failure to mount strong T-cell responses may be the primary cause of the progression of acute HTNV infection into severe HFRS ( 27 ). In our study, when remove the ELISPOT data of patients with severe/critical disease, the numbers of epitope VV9-specific CD8 + T cells were significantly larger than that in NC, indicating patients with milder disease may have more functional epitope-specific CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model of persistent infection, almost no IFN-γ-producing T cells were detected, while mice with transient infection showed increased functional HTNV-specific CTLs ( 23 , 47 ). HTNV-specific T-cell responses in patients with severe HFRS were heavily impaired at the early stage of infection, indicating that an initial failure to mount strong T-cell responses may be the primary cause of the progression of acute HTNV infection into severe HFRS ( 27 ). In our study, when remove the ELISPOT data of patients with severe/critical disease, the numbers of epitope VV9-specific CD8 + T cells were significantly larger than that in NC, indicating patients with milder disease may have more functional epitope-specific CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most HTNV-specific CTL epitopes identified are distributed on NP ( 6 , 27 , 28 ). Early research identified three CTL epitopes on HTNV NP ( 25 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical remission after severe HFRS is also associated with a sustained IFN-γ/granzyme B CD8 + T-cell response, even in the absence of detectable neutralizing antibodies [139]. In contrast, a low IFN-γ T-cell response is also associated with severe HFRS [140]. Among total T-cells, the CD8 + subset is responsible for the major response to HTNV peptides [45,140].…”
Section: Particular Characteristics Of the T-cell Response Againstmentioning
confidence: 99%
“…In contrast, a low IFN-γ T-cell response is also associated with severe HFRS [140]. Among total T-cells, the CD8 + subset is responsible for the major response to HTNV peptides [45,140]. Indeed, HTNV-specific CD8 + T-cells are required for efficient viral clearance in mice via production of IFN-γ, TNF-α, and cytotoxicity, and their low frequency leads to a persistent infection [141,142], such as seen in the hantavirus reservoir, deer mice [143].…”
Section: Particular Characteristics Of the T-cell Response Againstmentioning
confidence: 99%
“…However, immunodominant T cell responses are central in the control of any acute virus infection. A study reported weakening of IFN-γ- producing T cell response in patients with severe HFRS at the early stage of infection [ 47 ]. The study suggested that insufficient T cell response to the immunodominant epitopes might play a role in influencing the severity of HTNV infection.…”
Section: Discussionmentioning
confidence: 99%